THE CAPABILITIES OF RECONNAISSANCE COMPLEX WHEN USING UNMANNED AERIAL VEHICLES - Savin Evgeniy Vladimirovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article considers a wide range of capabilities provided by the reconnaissance complex when using unmanned aerial vehicles (UAVs). In particular, it emphasizes operational surveillance, reconnaissance and intelligence missions, operational support, monitoring and control, as well as data analysis and processing. Special attention is given to the advantages of UAVs in various fields, from military to civilian security. This work provides an overview of UAV capabilities in the context of reconnaissance complexes, which can be useful for specialists in defense, security, and intelligence.